Diatom size plasticity at regional and global scales - Pinto, Raquel Travincas (2020)
Studies based on diatom traits are increasing worldwide but most of them are based on database information from other geographical regions whereas data on direct observations and measurements of individuals are lacking. The aim of this study was to understand how diatom cell sizes vary at: 1) a small (regional) scale, among rivers and streams of Central Portugal with different hydromorphological and climatic characteristics (typologies) and 2) a large (global) spatial scale, comparing cell sizes from different areas of the world. For this study, species from 60 sites belonging to four Portuguese river types (Northern Mountain Streams – M; Littoral Rivers - L; Small Northern Rivers - N1 ≤ 100 km2; Medium-Large Northern Rivers - N1 > 100 km2) were studied. Only species with a relative abundance of 2.5 % or above were measured (length and width) and the length/width ratio was calculated, resulting in a total of 86 taxa and ≈3600 specimens measured. In parallel, a revision of published information and databases on the sizes of the analysed species was done considering information from Central and Northern Europe, North and South America, Asia, Africa and Antarctica. At the regional scale, 28 of the 36 species that were present in more than one river type showed significant differences in at least one measure studied. At a global scale, in general, diatoms’ lengths from Central Portugal differed from Central Europe, Northern Europe and Asia; also, diatoms’ lengths from Northern Europe differed from Africa and North America. At the species level, Achnanthidium minutissimum from Portugal was different from those of Africa and Asia; Achnanthidium subatomoides and Eolimna minima were different between Central Portugal and North America and Eunotia incisa differed between Central Europe and North America. Our results produced more adjusted information on diatom sizes of Central Portugal, which differed from some of the other world regions studied. Our conclusions indicate that not considering size plasticity in diatoms' ecological studies can lead to biased results and thus further studies are needed to investigate the spatial variability of diatom traits.